Effect of Enlightenment on the Attitude and Participation of Adolesecents to National Matters in Nigeria - Obafemi, F. A.; Akinseesin, O. A.; Obaoghe, T. O.; Shokoya, A. O.; Amosu, O. G.; Aruwa, M. C.; Ofoche, C. O. (Advances in Social Sciences Research Journal, 2022)
The aim of this study was to see how intervention of enlightenment about personal and national health plus wellbeing could impart the young ones concerning their attitude and participation in national matters. This study included college students from randomly selected urban and rural communities in Cross River, Edo, and Kaduna states. The current study enlisted a total of 140 participants. Structured pretested questionnaires were used to collect data. The majority of the respondents in the current study attributed health to wealth (35.4%), others defined health as total wellbeing (32.3%), clean and sanitary environment (6.3%), the fitness of mind and body (4.7%), state of wellness of mind, body, and financial ability (2.4%). 42.6% of the respondents in the current study indicated that they will improve on citizen responsibility; 19.7% said they will provide a sanitary environment whereas 12.6% indicated that good governance is necessary for the improved health of Nigeria; 5.5% noted that they staying healthy to improve the health of Nigeria; 11.8% stated that education is necessary for the nation’s improved health’ 7.9% indicated that they will improve basic amenities. The findings of this study point to an acceptance of increased citizen responsibility; the realization that the maintenance of basic amenities and the environment was critical for respondents to become aware of the growing role of the ordinary citizen in the provision and maintenance of good governance. Increased calls for Nigerians to register to vote have frequently failed to produce the desired results. According to the findings of the current study, the majority of respondents are eager to vote in the upcoming election.